Analyse comparative de l’état de conservation des forêts classées, des forêts communautaires et des forêts sacrées au Sud-Bénin (Afrique de l’Ouest) - GIBIGAYE ADAM, MOUSSA (My University, 2017)
This research aims to analyze the state of conservation of gazetted forest, community forest and sacred forest in the southern Benin. To do this, two gazetted forests, two communities forests and two sacred forests were chosen. The evaluation of the dynamics of the forest cover has been made of the comparative diachronic analysis of land cover in 1982 and 2015. The phytosociological and forest inventories were carried out in the forests studied. The results revealed that the areas of forest classes are held and sometimes experiencing an increase in the sacred forests while these forest classes experienced a regressive development in gazetted forests. In community forests, regression and maintaining forest classes were observed. The average density of trees is the highest recorded in the sacred forest of Zannouzoun (352.50 trees / ha) and the lowest density is achieved in the community forest Togbin-Daho (104.60 trees / ha). The highest Shannon diversity index is obtained in the sacred forest of Kodjizoun (3. 08 bits) while the lowest value of this index is recorded at the gazetted forests of Pahou (1.96 bit). The state and the evolutionary trend of forest cover and ecological parameters show that the sacred forests and incidentally community forests are best preserved as gazetted forests. However, the small size of sacred forests requires to qualify this conclusion.
Keywords: aires protégées; couvert forestier; paramètre écologique; tendance; Sud-Bénin.